The Use of the Canva Application as a Medium for Learning Arabic - Ramadhani, Indah Faqmi; Neeedad, Ahmeed; Jansee, Jansee (Journal International of Lingua and Technology, 2022)
Media in a classroom learning is needed by the teacher in explaining the material being taught to his students. The media can be in the form of writing or the use of audio or video applications. One of the applications that can be used to create a learning media using animated videos is the Canva application. Canva is an online application that is easy for teachers to use in helping the teaching process in the form of interesting, animated audio and video that doesn't make learning boring. So, the aim of this article is to give the ways to use Canva application for making some learning media. This research is research using qualitative methods. The application used in this study is the canva application which is used as a medium for learning Arabic class X Islamic high school al-Mumtaz Solok City. The result is an Arabic language learning media using the Canva application is an effective way to explain the material to students, especially at this time, where students only learn virtually.